Approaching an investigation of multi-dimensional inequality through the lenses of variety in models of capitalism - Gilberto Antonelli; Pinuccia Pasqualina Calia; Giovanni Guidetti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
After a synthetic presentation of the state of poverty and inequality in the world and the contradictions incurred by economic theory in this field after decades of globalization and in the midst of a persisting global crisis, in paragraphs 2. and 3. we outline the rational for our theoretical analysis, underlining two main aspects. First of all, in paragraph 2. we recall the reasons which makes inequality a multidimensional phenomenon, while in paragraph 3. we explore the reasons why the models of capitalism theory is relevant for studying multidimensional inequality. These paragraphs emphasise that inequality is a multidimensional and cumulative phenomenon and it should not be conceived only as the result of the processes of personal and functional distribution of income and wealth, which even by themselves are intrinsically multidimensional. The basic idea is that institutions, the cobweb of relations among them and their interaction with the economic structure define the model of capitalism which characterises a specific country and this, in turn, affects the level and the dynamics of inequality. This approach is consistent with the sociological approach by Rehbein and Souza (2014), based on the analytical framework developed by Pierre Bourdieu. In paragraph 4. we outline the rational for our empirical analysis, applying the notion of institutional complementarity and examining the relationship between institutional complementarity, models of capitalism and inequality. Besides, refining Amable's analysis (2003), we provide empirical evidence on the relationship between inequality in income distribution and models of capitalism. Additionally, basing on cluster analysis, we identify six different models of capitalism in a sample of OECD countries, provide preliminary evidence on the different level of inequality which characterises each model and suggest that no evidence supports of the idea that a single model of capitalism is taking shape in this sphere in EU. In paragraph 5. we give some hints about issues in search for a new interpretation capable to fasten together the process of increasing inequality, the notion of symbolic violence and the models of capitalism theory. In the last paragraph we focus on conclusions useful for carrying on our research agenda.
Keywords: P16; B52; 330